Support of Cultural Services Through the Integrated Service Centers: Prospects for Development - MALSHINA, Nataliya Anatol'evna; BRYNTSEV, Alexander Nikolaevich (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
The research deals with a problem of the regional development such as development and implementation of a mechanism, to support services culture. The notion of ‘integrated service center’ is discussed the article by the authors. The analysis is done of the existing domestic and foreign approaches regarding the definition of the cluster approach to the culture services in Russia. The key means of public-private partnerships in the cultural industries are highlighted in the research. A proposed method makes it possible to quickly response to changes in the environment and gets integrated into the economy of a particular region of the Russian Federation, to apply the logistic method in management and public-private partnership. Method of research includes the use of logistics principles to services culture, mathematical processing of statistical data and correlation – regression analysis. Approbation of the methodologies tools was which made in Saratov region, that possesses a sufficient economic potential for the development of culture services, and which demonstrates the improvement of socio-economic indicators while using integral service complexes. Based on the public-private partnership the proposed method allows to reduce budget expenditures for the culture services, to control the ratio and quality of free and paid services, to gain profit and implement internal reserves of cultural industry enterprises.